The Impact of Accounting Disclosure of Social Responsibility Practices in Protecting the Company’s Reputation During and After the Covid-19 Pandemic: An Applied Study - Basim Rashid Ali; Alaa Awad Kazim; Maram Fayez Mohammed (International Journal of Management Research and Economics, 2024)
The research aimed to identify the impact of accounting disclosure of social responsibility practices in its various dimensions in protecting the company's reputation during the Covid-19 pandemic. In order to achieve this, the researchers relied on the descriptive approach to frame the theoretical aspect and the analytical approach to complete the practical aspect by collecting data through a questionnaire prepared by the researchers. After collecting the data, it was analyzed using the statistical program (SPSS) for social sciences. Based on the theoretical and practical studies, the researchers reached some conclusions, including: Its importance stems from the fact that it is considered one of the ethical obligations in the first place, and thus it reflects the true social and human orientations of the owners, in one way or another, the true orientations of the owners socially and humanely. There is also a statistically significant moral correlation between accounting disclosure of social responsibility practices and the company's reputation. The research came out with a set of recommendations, the most important of which is that companies must develop clear and binding policies that reflect their commitment to social responsibility. Companies should also be transparent regarding their practices and efforts in the field of social responsibility.